2007
DOI: 10.1245/s10434-007-9719-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genetic Polymorphisms of GSTP1 313AG, MDR1 3435CC, and MTHFR 677CC Highly Correlated with Early Relapse of Breast Cancer Patients in Taiwan

Abstract: The results of the present study highly suggest that GSTP1, MDR1, and MTHFR genotypes could be prognostic factors for Taiwanese patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…This finding is similar to the Yogyakarta, Indonesian, 10 Khazakstan, 16 Chinese, 7 Taiwanese, 17 Brazilian, 18 and Italian. 19 But in Malay subjects from our http://mji.ui.ac.id data showed a significant deviated from HardyWeinberg equilibrium.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is similar to the Yogyakarta, Indonesian, 10 Khazakstan, 16 Chinese, 7 Taiwanese, 17 Brazilian, 18 and Italian. 19 But in Malay subjects from our http://mji.ui.ac.id data showed a significant deviated from HardyWeinberg equilibrium.…”
Section: Discussionsupporting
confidence: 83%
“…It means the study group could be heterogeneous thus may be different from other Persian population in Iran. It should be noted despite of different frequencies in present study from other Iranian ethnic groups which was reported by Rafiee in 2010 [19] there were no statistically significant differences (Iranian Georgian, χ 2 = 1.66, df = 1, p = 0.197 and Iranian Persian, χ 2 = 3.34, df = 1, p = 0.068).…”
Section: Discussioncontrasting
confidence: 52%
“…In our study the prevalence of GSTT1*0 was 25.5% .This result was slightly higher than Turkish, Mexican-Americans and Caucasians but lower than Chinese, Korean and Japanese ( Table 3). The reported frequency for other Iranian groups also presented significant differences between Iranian populations [19]. Iran is a big country with an estimated 70.5 million people that they are ethnically diverse.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Of those, 39 examined 1-3 polymorphisms 13,14,16,19,20,23,24,26-28,31,36,37,39-41,45,46,48,50,53,56,60-62,64,65,68,69,72-74,76-79,81,89,91 and 40 more than 3 polymorphisms 15,17,18,21,22,25,29,30,32-35,38,42-44,47,49,51,52,54,55,57-59,63,66,67,70,71,75,80,82-88,90. Fifty four studies examined the GSTM1 polymorphism 13,14,16,17,19-27,30-33,35,37,38,43-46,48,49,51-63,65,68,69,70,72-75,77,78,82,83,85-87, 57 the GSTP1 Ile105Val polymorphism 13-16,18,21,22,…”
Section: Resultsmentioning
confidence: 99%